MAIT cells reside in the female genital mucosa and are biased towards IL-17 and IL-22 production in response to bacterial stimulation - Gibbs, A.; Leeansyah, E.; Introini, A.; Paquin-Proulx, D.; Hasselrot, K.; Andersson, E.; Broliden, K.; Sandberg, J.K.; Tjernlund, A. (Mucosal immunology, 2017)
The female genital tract (FGT) mucosa is a critically important site for immune defense against microbes. Mucosal-associated invariant T (MAIT) cells are an innate-like T-cell population that recognizes microbial riboflavin metabolite antigens in an MR1-dependent manner. The role of MAIT cells in the FGT mucosa is unknown. Here, we found that MAIT cells and MR1+ antigen-presenting cells were present in the upper and lower FGT, with distinct tissue localization of MAIT cells in endometrium vs. cervix. The MAIT cells from the FGT and blood displayed a distinct phenotype with expression of interleukin (IL)-18Rα, CD127, α4β7, PD-1, as well as the transcription factors promyelocytic leukemia zinc finger (PLZF), RORγt, Helios, Eomes, and T-bet. Their expression levels of PLZF and Eomes were lower in the FGT compared with blood. When stimulated with Escherichia coli, MAIT cells from the FGT displayed a bias towards IL-17 and IL-22 expression, whereas blood MAIT cells produced primarily IFN-γ, TNF, and Granzyme B. Furthermore, both FGT- and blood-derived MAIT cells were polyfunctional and contributed to the T-cell-mediated response to E. coli. Thus, MAIT cells in the genital mucosa have a distinct IL-17/IL-22 profile and may have an important role in the immunological homeostasis and control of microbes at this site.